Ofício do magistrado do distrito de Xiangshan, Yang, ao procurador de Macau, sobre a compra de rapé (1776)
This imperial edict, dated 16th day of the fifth lunar month in the sixty-first year of the Kangxi Emperor’s reign (1722 CE), and reissued with marginalia referencing the forty-first year of the Qianlong reign (1776 CE), is a formal administrative directive issued by Magistrate Yang of Xiangshan County to Wei Luo Duo, the Foreign Headman in Macau. The document concerns the regulation of foreign merchants resident in Macau and their trading vessels, specifically addressing the consignment of opium—measured in *lā*, a local unit approximating 0.57 kg—and snuff (*rapé*), identified with its Portuguese term and literal translation. It instructs the Foreign Headman to ensure that over four hundred *lā* of opium be reserved for official collection by county officers, who would subsequently settle the agreed price; merchants are explicitly prohibited from delaying or withholding delivery. The edict notes repeated deferrals causing administrative delay and adverse impact upon the tribute ceremony, which it deems unsuitable. Marginal annotations indicate archival classification (T4/, T41) and identification numbers (No. 168; Person No. 76). The text bears an official red square seal of indeterminate inscription. As a primary source, this document provides direct evidence of Qing dynasty provincial oversight of foreign trade, opium procurement practices, bureaucratic protocol, and Sino-Portuguese administrative interaction in Macau during the early eighteenth century.
Keywords: Archival Marginalia and Seals; Historical Measurement Units in Qing Documents; Macau Foreign Headman; Opium Consignment Restrictions; Qing Dynasty administrative directive; Regulation of Foreign Merchants in Macau; Sino-Portuguese Trade Provenance; Snuff Trade Regulation; Transcription; Xiangshan County Magisterial Authority